Neuroprotective Effect of Bauhinia variegata Leaf Extract against Colchicine: An Experimental Study on Cognitive Dysfunction and Biochemical Alterations in Mice - Khare, Pragati; Kishore, Kamal; Sharma, Dinesh Kumar (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: To study the protective role of Bauhinia variegata ethanolic leaf extract induced by colchicine cognitive dysfunction and the damage of oxidative in Swiss albino mice; to examine the neuroprotective consequence of Bauhinia variegata by conducting behavioral memory tests and to estimate the biochemical parameters by using brain homogenate. Methods: The research was conducted on colchicine induced model for a period of 28 days (4 weeks). Behavioral research was conducted using Elevated plus maze, Passive evasion Paradigm, Morris water maze and Actophotometer; thus biochemical parameters of brain homogenate such as acetyl cholinesterase (AChE), total protein, lipid peroxidation (MDA) and glutathione (GSH) were estimated. Swiss albino mice (48) were distributed into eight sets, each constituting 6 mice. Class I got carboxy methyl cellulose 1 per cent w/v. Group II piracetam was administered i.p. (200 milligrams / kg). Group III obtained 1 mg / kg of colchicine i.c.v. Group IV and V were provided with 200 and 400 mg / kg of ethanolic Bauhinia variegata leaf extract. Group VI was administered Piracetam (200 mg / kg, i.p.) to mice each day for 28 days continuously. Colchicine 1 mg / kg, i.p., at 60 min after 28th day piracetam injection was injected. Group VII and VIII received 200 and 400 mg / kg oral ethanolic Bauhinia variegata leaf extract for 28 consecutive days, and colchicine (1 mg / kg) was injected i.c.v at 90 min after extract administration on the 28th day. All the data and information were examined and analyzed through the use of ANOVA which is One-way then by a check by Tukey’s test. Results: The Bauhinia variegata leaf extract showed substantial reduction in raised plus maze and morris water maze transfer latency. It showed a marked increase in passive avoidance paradigm transfer latency. The administration of ethanolic Bauhinia variegata leaf extract (200mg/kg and 400mg/kg) indicated a substantial increase (P<0.001) in acetylcholinesterase and GSH levels, a significant reduction (P<0.001) in total protein, NO and MDA. Conclusion: This study shows ethanolic leaf extract of Bauhinia variegata has a neuroprotective effect against memory loss caused by colchicine.
Keywords: Bauhinia variegata; Neuroprotective; Alzheimer’s disease; Colchicine